Band-gap dependence of three-photon absorption in NiO nanoparticles synthesized at different calcination temperatures. (February 2023) - Pradeep Kumar, V; Pradeep, C; Raj Sha, M M; Radhakrishnan, P; Mujeeb, A
Highlights: The first paper discusses the three-photon absorption mechanism of nickel oxide nanoparticles. The nickel oxide nanoparticles of various bandgaps are prepared using the chemical precipitation process. The three-photon absorption coefficient has been found to increase as the bandgap is reduced. The three-photon absorption cross-sections has been determined to be 3.53 10 -78 cm 6 s 2 /photon 2 . The lifespan analysis and the mechanism of free-carrier absorption are also investigated. Abstract: The nonlinear optical properties of nickel oxide (NiO) nanoparticles were investigated using Z-scan technique with a fundamental nanosecond Nd:YAG laser. The nanoparticles were prepared using chemical precipitation method and its band-gap was varied by adopting different calcination temperature. We found an analytical result for the three-photon absorption coefficient inversely proportional to the band-gap based on the theory predicted from the wherret's equation for parabolic bands. The three-photon absorption coefficient and the extracted three-photon absorption cross-section were obtained to be 81.60 cm 3 /GW 2 and 3.53 × 10 -78 cm 6 s 2 /photon 2 at a calcination temperature of 400˚C.